HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG INTERPRETASI KMS DENGAN BERAT BADAN BALITA USIA 12 BULAN S/D 59 BULAN DI POSYANDU DESA JOKARTO KECAMATAN TEMPEH KABUPATEN LUMAJANG - Wulan Laras Sari, Ika; Zakiyyah, Muthmainnah; Wahyuningsih, Sri (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
Toddler weight is a measure of toddler growth KMS is a media used to assess toddlers’ growth and development. A mother’s knowledge regarding the interpretation of KMS is an important thing to pay attention to because the mother is the first spearhead in understanding her toddler nutritional status. The purpose of this research was to analyze correlation between the level of mothers’ knowledge about the interpretation KMS and toddlers’ weight (12-59 months) at Posyandu Jokarto village. The research method used is an analytic observational research method with a cross-sectional approach. Sampling using simple random sampling, the number of samples is 75 respondents. The research instrument used a questionnaire. The results showed that most of the respondents had good category knowledge about the interpretation of KMS, namely experiencing toddler weight gain (96.9%). The statistical test results using Spearman Rho obtained a value of 0.590 with a significance of 0.000 (<0.05). From these results, Ho was declared rejected, which means that there is a fairly strong and significant correlation between the level of knowledge of the mother about the interpretation of KMS and the weight of the toddler (12-59 months). Respondents are expected to regularly participate in posyandu activities and be more active in asking midwives regarding the interpretation of KMS and toddler nutrition. Can be a useful reference for further research related to mother's knowledge about the interpretation of KMS with toddler weight.